High Dynamic Range Photography and Videography : Approaches, Problems and Chances - Berg, Oksana; Hahn, Stefan
High Dynamic Range (HDR) imaging is the latest approach to capture and display the real world lifelike and with highest precision in digital form. In contrast to ordinary photo / video cameras and output devices like CRTs or LCDs, the HDR technology offers an unknown extended contrast ratio and color richness. It is supposed to represent the original lighting situation of a scene including all details in the shadows and the lights as it was perceived by a human in the moment of shooting the digital image. HDR pictures and videos are promised to boost the sensation of digital content in a way, typical recording and presentation systems cannot achieve. In this Master Thesis the fundamentals and the possible fields of application of HDR are presented and evaluated. Besides a comprehensive overview about advantages and deficiencies of capturing and display technologies a deeper look inside the HDR image processing and encoding is given. The additional case study shows the experimental transfer of HDR still image generation techniques to the area of video. The occurred technical and methodical problems and final results are discussed in detail and finally, the future appliance of HDR in photography and videography is outlined.
Keywords: Photographie; Video